The Cleansing Effect of Recessions - Caballero, Ricardo J.; Hammour, Mohamad L. (American Economic Review, 1994)
We investigate industry response to cyclical variations in demand. Production units that embody the newest process and product innovations are continuously being created, and outdated units are being destroyed. Although outdated units are the most likely to turn unprofitable and be scrapped in a recession, they can be "insulated" from the fall in demand by a reduction in creation. The structure of adjustment costs plays a determinant role in the responsiveness of those two margins. The calibrated model matches the relative volatilities of the observed manufacturing job creation and destruction series, and their asymmetries over the cycle.